2013
DOI: 10.1002/jbm.a.34954
|View full text |Cite
|
Sign up to set email alerts
|

Influence of osteocytes in the in vitro and in vivo β‐tricalcium phosphate‐stimulated osteogenesis

Abstract: Osteocytes, known to act as the main regulators of bone homeostasis, have become a major focus in the field of bone research. Bioactive ceramics have been widely used for bone regeneration. However, there are few studies about the interaction of osteocytes with bioceramics. The effects of osteocytes on the in vitro and in vivo osteogenesis of bioceramics are also unclear. The aim of this study was to investigate the role of osteocytes on the β-tricalcium phosphate (β-TCP) stimulated osteogenesis. It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…This protein is also necessary for osteocyte dendrite elongation in response to shear stress . As dendrite formation is an active process and not a passive mechanism, it is likely that the podoplanin protein is critical not only during dendritic formation, but also for osteocyte viability and function, and, therefore, essential for normal bone physiology . In our samples, we found that the podoplanin expression is evident in both groups, demonstrating that even at the early time point, the osteocytes development, function, and expansion within the grafted area are clear.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This protein is also necessary for osteocyte dendrite elongation in response to shear stress . As dendrite formation is an active process and not a passive mechanism, it is likely that the podoplanin protein is critical not only during dendritic formation, but also for osteocyte viability and function, and, therefore, essential for normal bone physiology . In our samples, we found that the podoplanin expression is evident in both groups, demonstrating that even at the early time point, the osteocytes development, function, and expansion within the grafted area are clear.…”
Section: Discussionmentioning
confidence: 54%
“…34 As dendrite formation is an active process and not a passive mechanism, it is likely that the podoplanin protein is critical not only during dendritic formation, but also for osteocyte viability and function, and, therefore, essential for normal bone physiology. 34,[80][81][82][83][84][85] In our samples, we found that the podoplanin expression is evident in both groups, demonstrating that even at the early time point, the osteocytes development, function, and expansion within the grafted area are clear. Furthermore, this finding suggests that this important feature of normal bone function is being developed in areas grafted with allogeneic material.…”
Section: Graph 5 Correlation Between Of the Number Of Lost Implants Amentioning
confidence: 51%
“…RAW cells/coating materials CMs were prepared by mixing the supernatants with complete medium at a ratio of 1:2 and were stored at -80 ºC for the subsequent experiments [25,41].…”
Section: Ionic Concentrations Of the Preparation Of Raw Cells/coatingmentioning
confidence: 99%
“…Mouse long bone osteocyte-like cells MLO-Y4 and IDG-SW3 express podoplanin more strongly than MC3T3-E1 (20)(21)(22)(23). Differentiation of cultured mouse calvarial osteoblasts and pre-osteoblastoid cell MLO-A5 into osteocytes in calcification medium containing βglycerophosphate and ascorbic acid, and biomaterial-induced calcification are simultaneously accompanied by an increase in podoplanin (24)(25)(26)(27). Also, in the mature osteoblast MLO-A5 cell line, an increase in podoplanin coincides with dendrite formation, calcification, and RhoA activation (28).…”
Section: Introductionmentioning
confidence: 99%